Thermally conductive composition, thermally conductive sheet using same, and method for producing thermally conductive sheet

By using thermally conductive particles of specific types and particle sizes in the thermally conductive composition, and using manufacturing methods such as vacuum defoaming and rolling, the problems of plasticity and forming processability of the thermally conductive sheet when improving thermal conductivity are solved, and efficient thermally conductive composition and sheet are achieved.

CN119855874APending Publication Date: 2025-04-18FUJI POLYMER INDUSTRIES CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202480003945.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-11-17
Filing Date
2024-04-08
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

While the conventional thermal conductivity composition and the thermal conductivity sheet used therewith have improved thermal conductivity, the plasticity of the composition becomes higher and the molding processability becomes worse.

Method used

The thermally conductive sheet is made by a manufacturing method of vacuum defoaming, rolling and heat curing using a thermally conductive composition containing a matrix resin formed by a thermosetting resin, a curing catalyst and a specific type, particle size and added amount of thermally conductive particles.

Benefits of technology

The thermal conductivity composition and sheet with high thermal conductivity, low plasticity of the composition and good forming processability are achieved, and are suitable as an efficient heat dissipation material between electrical/electronic components and heat dissipation bodies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119855874A_ABST
    Figure CN119855874A_ABST
Patent Text Reader

Abstract

The heat-conducting resin composition includes a matrix resin (component A) formed from a thermosetting resin, a curing catalyst, and heat-conducting particles, the heat-conducting particles including the following components B and C. (1) component B: containing 220-500 parts by mass of alumina having a cumulative particle size distribution D50 (median diameter) of 0.01 [mu] m or more and less than 1 [mu] m on a volume basis per 100 parts by mass of the matrix resin; and (2) component C: containing 1900-2500 parts by mass of aluminum nitride having a D50 (median particle diameter) of 0.01-150 [mu] m (inclusive) per 100 parts by mass of the matrix resin, thereby providing a thermally conductive composition having high thermal conductivity, low plasticity, and good moldability, a thermally conductive sheet using the same, and a method for producing the thermally conductive sheet.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a thermally conductive composition suitable for interposing between a heat generating portion of an electric or electronic component and a heat sink, a thermally conductive sheet using the composition, and a method for producing the composition. Background Art

[0002] In recent years, the performance of semiconductors such as CPUs has improved significantly, and the amount of heat generated has also become huge. Therefore, a heat sink is installed on the heat-generating electronic components, and a thermally conductive sheet is used to improve the adhesion between the semiconductor and the heat sink. With the miniaturization, high performance, and high integration of equipment, thermally conductive sheets are required to have flexibility and high thermal conductivity. In the past, patent documents 1 to 4 have been proposed as thermally conductive sheets. Furthermore, the applicant proposed a thermally conductive sheet with high thermal conductivity in patent document 5.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application No. 2021-518466

[0006] Patent Document 2: Japanese Patent Application No. 2020-137970

[0007] Patent Document 3: Japanese Patent Application No. 2018-088416

[0008] Patent Document 4: Japanese Patent Application Publication No. 2016-216523

[0009] Patent Document 5: Japanese Patent No. 7061736 Summary of the invention

[0010] Problems to be solved by the invention

[0011] However, conventional thermally conductive compositions and thermally conductive sheets using the same have the following problem: when the thermal conductivity is increased, the plasticity of the composition increases, and the molding processability deteriorates. This is because in order to increase the thermal conductivity, a large amount of thermally conductive particles must be added, which increases the plasticity of the composition and deteriorates the molding processability.

[0012] The present invention aims to solve the above-mentioned conventional problems and provides a thermally conductive composition having high thermal conductivity, low plasticity of the composition and good molding processability, a thermally conductive sheet using the same, and a method for producing the same.

[0013] Means for solving problems

[0014] The thermally conductive composition of the present invention is a thermally conductive composition comprising a matrix resin (component A) formed of a thermosetting resin, a curing catalyst, and thermally conductive particles, wherein the thermally conductive particles comprise the following components B and C.

[0015] (1) Component B: 220 to 500 parts by mass of aluminum oxide having a D50 (median diameter) of 0.01 μm or more and less than 1 μm in cumulative particle size distribution on a volume basis, based on 100 parts by mass of the matrix resin, comprising the following components B-1 and B-2,

[0016] Component B-1: 30 to 100% by mass of component B with respect to 100% by mass of component B having a D50 (median diameter) of 0.01 μm or more and less than 0.3 μm, and a BET specific surface area of ​​9 m 2 / g or more of aluminum oxide,

[0017] Component B-2: 0 to 70% by mass of aluminum oxide having a D50 (median diameter) of 0.3 μm or more and less than 1 μm, relative to 100% by mass of component B,

[0018] (2) Component C: 1900 to 2500 parts by mass of aluminum nitride having a D50 (median particle size) of 0.01 μm or more and 150 μm or less, based on 100 parts by mass of the matrix resin, including the following components C-1 and C-2,

[0019] C-1 component: D50 (median particle size) is 0.01 μm or more and less than 30 μm,

[0020] Component C-2: D50 (median diameter) is 30 μm or more and 150 μm or less.

[0021] The thermally conductive sheet of the present invention is characterized in that the thermally conductive composition is formed into a sheet.

[0022] The method for producing the thermally conductive sheet of the present invention comprises vacuum degassing the thermally conductive composition, rolling it, forming it into a sheet, and then heating and curing it to produce the thermally conductive sheet.

[0023] Effects of the Invention

[0024] The present invention can provide a thermally conductive composition having high thermal conductivity, low plasticity of the composition, and good forming processability and a thermally conductive sheet using the same by setting the above composition. That is, by specifying the type, particle size, and addition amount of the conductive particles, a thermally conductive composition having high thermal conductivity, low plasticity of the composition, and good forming processability can be prepared. Specifically, the plasticity of the thermally conductive composition after degassing before curing is preferably less than 100, and the preferred thermal conductivity is 14W / m·K or more. In addition, the method for manufacturing the thermally conductive sheet of the present invention can be formed into a continuous sheet because the composition has low plasticity and good forming processability. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] [ Figure 1 ] Figure 1 This is a schematic cross-sectional view showing a method of using a thermally conductive sheet in one embodiment of the present invention.

[0026] [ Figure 2 ] Figure 2 A and B are schematic explanatory diagrams showing a method for measuring the thermal conductivity of a sample in one example of the present invention. DETAILED DESCRIPTION

[0027] The present invention is a thermally conductive composition comprising a matrix resin, a curing catalyst and thermally conductive particles. The matrix resin is preferably a thermosetting resin such as silicone rubber, silicone gel, acrylic rubber, fluororubber, epoxy resin, phenolic resin, unsaturated polyester resin, melamine resin, acrylic resin, silicone resin, fluororesin, etc. Among them, silicone is preferred, which is an elastomer, gel, putty or grease. The curing system of silicone can use any method such as peroxide, addition, condensation, etc. Silicone is preferred due to its high heat resistance. In addition, it is preferably an addition reaction type due to the reasons that there is no corrosion to the surroundings, there are few by-products released outside the system, and it can be reliably cured to a deep part.

[0028] The thermally conductive particles are as follows with respect to 100 parts by mass of the matrix resin (component A).

[0029] (1) Component B: 220 to 500 parts by mass of aluminum oxide having a volume-based cumulative particle size distribution D50 (median diameter) of 0.01 μm or more and less than 1 μm is added to 100 parts by mass of the matrix resin. The preferred amount is 230 to 480 parts by mass, and the more preferred amount is 240 to 440 parts by mass.

[0030] In addition, the component B contains the following component B-1 and component B-2.

[0031] Component B-1: D50 (median particle size) of 0.01 μm or more and less than 0.3 μm, BET specific surface area of ​​9 m 2 / g or more of aluminum oxide, and 30 to 100% by mass relative to 100% by mass of component B. A preferred D50 (median particle size) is 0.1 μm or more and less than 0.3 μm. In addition, a preferred BET specific surface area is 9 to 20 m 2 / g, more preferably 10 to 18 m 2 It should be noted that the BET specific surface area is measured in accordance with the provisions of JIS R 1626-1996.

[0032] Component B-2: Alumina having a D50 (median diameter) of 0.3 μm or more and less than 1 μm, which accounts for 0 to 70% by mass based on 100% by mass of component B. Preferably, D50 (median diameter) is 0.3 μm or more and 1.0 μm or less.

[0033] (2) Component C: 1900 to 2500 parts by mass of aluminum nitride having a D50 (median particle size) of 0.01 μm or more and 150 μm or less is added to 100 parts by mass of the matrix resin. The preferred D50 (median particle size) is 0.1 μm or more and 120 μm or less. The preferred amount added is 1920 to 2400 parts by mass, and the more preferred amount added is 1940 to 2300 parts by mass.

[0034] In addition, the component C includes the following component C-1 and component C-2.

[0035] Component C-1: D50 (median particle size) is 0.01 μm or more and less than 30 μm

[0036] · Component C-2: D50 (median particle size) is 30 μm or more and 150 μm or less.

[0037] In the present invention, a plurality of inorganic particles having different average particle sizes are used as thermally conductive particles. Thus, thermally conductive inorganic particles having small particle sizes are buried between large particles, and filling can be performed in a state close to the closest packing, thereby obtaining a thermally conductive composition having high thermal conductivity, low plasticity of the composition, and good molding processability.

[0038] The mass ratio of the C-1 component to the C-2 component is preferably C-2 component ≤ C-1 component, and more preferably C-2 component < C-1 component. Thus, a thermally conductive composition having high thermal conductivity, low plasticity of the composition, and good molding processability can be obtained.

[0039] In addition, the plasticity after vacuum degassing before curing of the thermally conductive composition is preferably less than 100, more preferably 10 to 99, further preferably 20 to 99, and particularly preferably 30 to 99. Thus, a thermally conductive composition with low plasticity and good forming processability can be obtained. Regarding plasticity, according to JIS K 6300-3, ISO2007: 1991, using a Wallace plastometer, at a measuring temperature of 25°C, the thickness (t) after compressing the sample between two metal plates with a certain load (100N) and a certain time (15 seconds) is divided by the thickness (t0) before compression, and the plasticity is obtained by plasticity (P0 = t / t0 × 100). The smaller P0 is, the softer it is. In addition, a small value of plasticity (P0) is synonymous with low plasticity.

[0040] The thermal conductivity of the cured product of the thermally conductive composition is preferably 14 W / m·K or more, more preferably 14 to 20 W / m·K, and further preferably 14.5 to 20 W / m·K. This increases the thermal conductivity and is suitable as a heat dissipation sheet: TIM (Thermal Interface Material).

[0041] The SHORE 00 hardness of the cured product of the thermally conductive composition is preferably 75 or less, more preferably 10 to 75, and still more preferably 15 to 72. This improves the conformability to the heat generating body and the heat dissipating body (heat absorber).

[0042] The matrix resin is preferably at least one selected from the group consisting of an addition-curable silicone polymer, a peroxide-curable silicone polymer, and a condensation-type silicone polymer.

[0043] It is preferred to further add 0.1 to 10 parts by mass of a silane coupling agent to 100 parts by mass of the above-mentioned matrix resin, and it is more preferred to add 0.5 to 7 parts by mass. The silane coupling agent is coated on the surface of the thermally conductive particles (surface treatment), is easily filled into the matrix resin (plasticizer function), and has the effect of preventing the curing catalyst from being adsorbed on the thermally conductive particles and preventing curing from being hindered. This is useful for storage stability. Silane coupling agents include R(CH3) a Si(OR') 4-a (R is an unsubstituted or substituted organic group having 1 to 20 carbon atoms, R' is an alkyl group having 1 to 4 carbon atoms, and a is 0 or 1) or a partial hydrolyzate thereof. R(CH3) a Si(OR') 4-a(R is an unsubstituted or substituted organic group having 1 to 20 carbon atoms, R' is an alkyl group having 1 to 4 carbon atoms, and a is 0 or 1) is represented by an alkoxysilane compound (hereinafter referred to as "silane"), for example, methyltrimethoxysilane, ethyltrimethoxysilane, propyltrimethoxysilane, butyltrimethoxysilane, pentyltrimethoxysilane, hexyltrimethoxysilane, hexyltriethoxysilane, octyltrimethoxysilane, octyltriethoxysilane, decyltrimethoxysilane, decyltriethoxysilane, dodecyltrimethoxysilane, dodecyltriethoxysilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane, octadecyltrimethoxysilane, octadecyltriethoxysilane and the like silane compounds. The above silane compounds can be used alone or in combination of two or more.

[0044] At least one component selected from the group consisting of aluminum oxide (aluminum oxide) as the above-mentioned component B and aluminum nitride as the component C is preferably amorphous crushed particles. Amorphous crushed particles are easy to obtain. Hereinafter, amorphous crushed particles are also simply referred to as amorphous.

[0045] The thermally conductive composition of the present invention has high versatility and is suitable as a TIM if it is formed into a sheet as a thermally conductive sheet. The thickness of the thermally conductive sheet is preferably in the range of 0.2 to 10 mm.

[0046] In the method for manufacturing a thermally conductive sheet of the present invention, the thermally conductive composition is subjected to vacuum degassing, rolling, sheet forming, and then heated and cured to form a thermally conductive sheet. Vacuum degassing is to reduce the pressure of the thermally conductive composition (composite) to -0.08 to -0.1 Pa and leave it for about 5 to 10 minutes for degassing. Rolling includes rolling processing, stamping processing, etc., but rolling processing can be continuously produced, so rolling processing is preferred.

[0047] The dielectric breakdown voltage (JIS K 6249) of the thermally conductive composition is preferably 7 to 16 kV / mm. This allows the composition to be a thermally conductive sheet having high electrical insulation properties.

[0048] The volume resistivity (JIS K 6249) of the thermally conductive composition is preferably 10 10 ~10 14 Ω·cm. This can produce a thermally conductive sheet with high electrical insulation properties.

[0049] As an example of the present invention, in the case of an addition reaction type silicone composition (uncured composition), a composite having the following composition is preferred.

[0050] ABase resin

[0051] The matrix resin contains the following (A1) (A2).

[0052] (A1) Base polymer component: a linear organopolysiloxane containing at least two alkenyl groups bonded to silicon atoms in one molecule

[0053] (A2) crosslinking component: an organohydrogenpolysiloxane containing at least two hydrogen atoms bonded to silicon atoms in one molecule, in an amount of less than 1 mol per 1 mol of the silicon-bonded alkenyl groups in the component A.

[0054] In addition to the above components (A1) and (A2), an organopolysiloxane having no reactive group may be contained, such as unreacted silicone oil, for example, dimethylpolysiloxane.

[0055] In the present specification, the total amount of the base polymer component (A1), the crosslinking component (A2), the unreacted silicone oil and the silane coupling agent is 100 parts by mass.

[0056] B Thermally conductive particles: as described above.

[0057] C Platinum metal catalyst: 0.01 to 1000 ppm by mass relative to the base resin

[0058] D Other additives: silane coupling agent, curing delay agent, colorant, etc.; any amount

[0059] Hereinafter, each component will be described.

[0060] (1) Base polymer component (component A1)

[0061] The base polymer component is an organopolysiloxane containing two or more alkenyl groups bonded to silicon atoms in one molecule, and the organopolysiloxane containing two or more alkenyl groups is the main agent (base polymer component) in the silicone rubber composition of the present invention. The organopolysiloxane has two alkenyl groups such as vinyl groups and allyl groups with 2 to 8 carbon atoms, especially 2 to 6 alkenyl groups bonded to silicon atoms as alkenyl groups in one molecule. From the perspective of operability, curability, etc., the viscosity is preferably 10 to 1,000,000 mPa·s at 25°C, and is particularly preferably 100 to 100,000 mPa·s.

[0062] Specifically, an organopolysiloxane having two or more alkenyl groups bonded to the silicon atom at the end of the molecular chain in one molecule as shown in the following general formula (chemical formula 1) is used. The side chain is a straight-chain organopolysiloxane terminated with an alkyl group. From the perspective of operability, curability, etc., the viscosity at 25° C. is preferably 10 to 1,000,000 mPa·s. In addition, the straight-chain organopolysiloxane may also contain a small amount of branched structure (trifunctional siloxane unit) in the molecular chain.

[0063] [Chemical formula 1]

[0064]

[0065] In the formula, R 1 are unsubstituted or substituted monovalent hydrocarbon groups that are the same or different from each other and do not have an aliphatic unsaturated bond, R 2 is an alkenyl group, and k is 0 or a positive integer. 1 An unsubstituted or substituted monovalent hydrocarbon group having no aliphatic unsaturated bond, for example, a monovalent hydrocarbon group having 1 to 10 carbon atoms, particularly 1 to 6 carbon atoms, specifically, alkyl groups such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, neopentyl, hexyl, cyclohexyl, octyl, nonyl, decyl, aryl groups such as phenyl, tolyl, xylyl, naphthyl, aralkyl groups such as benzyl, phenylethyl, phenylpropyl, and groups in which a part or all of the hydrogen atoms of these groups are replaced by halogen atoms such as fluorine, bromine, chlorine, cyano, etc., for example, halogen-substituted alkyl groups such as chloromethyl, chloropropyl, bromoethyl, trifluoropropyl, cyanoethyl, etc. are mentioned. As R 2 The alkenyl group is preferably an alkenyl group having 2 to 6 carbon atoms, particularly 2 to 3 carbon atoms, and specifically, vinyl, allyl, propenyl, isopropenyl, butenyl, isobutenyl, hexenyl, cyclohexenyl, etc., preferably vinyl. In the general formula (1), k is usually 0 or a positive integer satisfying 0≤k≤10000, preferably an integer satisfying 5≤k≤2000, and more preferably an integer satisfying 10≤k≤1200.

[0066] The organopolysiloxane as component A1 may be an organopolysiloxane having 3 or more, usually 3 to 30, preferably about 3 to 20, alkenyl groups such as vinyl and allyl groups having 2 to 8 carbon atoms, especially 2 to 6, bonded to silicon atoms in one molecule. The molecular structure may be any of linear, cyclic, branched, and three-dimensional network structures. Preferably, the main chain is a linear organopolysiloxane having a repeating structure of a diorganosiloxane unit, both ends of the molecular chain are capped with triorganosiloxy groups, and the viscosity at 25°C is 10 to 1,000,000 mPa·s, especially 100 to 100,000 mPa·s.

[0067] The alkenyl group can be bonded to any part of the molecule. For example, an alkenyl group bonded to a silicon atom at a molecular chain end or a non-terminal molecular chain (in the middle of the molecular chain) may be included. Among them, there are 1 to 3 alkenyl groups on the silicon atoms at both ends of the molecular chain represented by the following general formula (chemical 2), wherein when the alkenyl groups bonded to the silicon atoms at the ends of the molecular chain are less than 3 in total at both ends, in terms of workability, curability, etc., it is preferred to have at least one alkenyl group bonded to the silicon atom at a non-terminal molecular chain (in the middle of the molecular chain) (for example, as a substituent in a diorganosiloxane unit) Straight-chain organopolysiloxane, and as mentioned above, the viscosity at 25°C is 10mPa·s to 1000000mPa·s. In addition, the straight-chain organopolysiloxane may also contain a small amount of branched structure (trifunctional siloxane unit) in the molecular chain.

[0068] [Chemical formula 2]

[0069]

[0070] In the formula, R 3 are unsubstituted or substituted monovalent hydrocarbon groups which are the same or different from each other, and at least one of them is an alkenyl group. 4 are unsubstituted or substituted monovalent hydrocarbon groups that are the same or different from each other and do not have an aliphatic unsaturated bond, R 5 is an alkenyl group, and l and m are 0 or positive integers. 3 The monovalent hydrocarbon group is preferably a monovalent hydrocarbon group having 1 to 10 carbon atoms, particularly 1 to 6 carbon atoms. Specifically, alkyl groups such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, neopentyl, hexyl, cyclohexyl, octyl, nonyl and decyl can be listed; aryl groups such as phenyl, tolyl, xylyl and naphthyl; aralkyl groups such as benzyl, phenylethyl and phenylpropyl; alkenyl groups such as vinyl, allyl, propenyl, isopropenyl, butenyl, hexenyl, cyclohexenyl and octenyl; groups in which a part or all of the hydrogen atoms of these groups are substituted by halogen atoms such as fluorine, bromine and chlorine, cyano and the like, for example, halogen-substituted alkyl groups such as chloromethyl, chloropropyl, bromoethyl and trifluoropropyl, cyanoethyl and the like.

[0071] In addition, as R 4 A monovalent hydrocarbon group having 1 to 10 carbon atoms, particularly preferably a monovalent hydrocarbon group having 1 to 6 carbon atoms, can be exemplified by the same group as R 1 Specific examples of R are the same monovalent hydrocarbon groups, but do not include alkenyl groups. 5 The alkenyl group is preferably an alkenyl group having 2 to 6 carbon atoms, and particularly preferably an alkenyl group having 2 to 3 carbon atoms. Specifically, the alkenyl group having the same R as in the above formula (Chemical Formula 1) can be exemplified. 2The same alkenyl group, preferably vinyl. l and m are usually 0 or positive integers satisfying 0 < l + m ≤ 10000, preferably 5 ≤ l + m ≤ 2000, more preferably 10 ≤ l + m ≤ 1200, and are integers satisfying 0 < l / (l + m) ≤ 0.2, preferably 0.0011 ≤ l / (l + m) ≤ 0.1.

[0072] (2) Crosslinking component (Component A2)

[0073] The organohydrogenpolysiloxane of Component A2 of the present invention functions as a crosslinking agent, and a cured product is formed by the addition reaction (hydrosilylation) of the SiH group in this component and the alkenyl group in Component A. Any organohydrogenpolysiloxane can be used as long as it has two or more hydrogen atoms bonded to silicon atoms (i.e., SiH groups) in one molecule. The molecular structure of this organohydrogenpolysiloxane can be any of linear, cyclic, branched, and three-dimensional network structures. An organohydrogenpolysiloxane having 2 to 1000, particularly about 2 to 300 silicon atoms (i.e., degree of polymerization) in one molecule can be used.

[0074] The position of the silicon atom bonded to the hydrogen atom is not particularly limited and can be at the end of the molecular chain or non-terminal (in the middle of the molecular chain). In addition, as the organic group bonded to the silicon atom other than the hydrogen atom, an unsubstituted or substituted monovalent hydrocarbon group having no aliphatic unsaturated bond as described above for R in the above general formula (Chemical formula 1) can be cited. 1 The same unsubstituted or substituted monovalent hydrocarbon group having no aliphatic unsaturated bond.

[0075] As the organohydrogenpolysiloxane of Component A2, an organohydrogenpolysiloxane having the following structure can be exemplified.

[0076] [Chemical formula 3]

[0077]

[0078] In the above formula, R 6 is an alkyl group, phenyl group, epoxy group, acryloyl group, methacryloyl group, alkoxy group, or hydrogen atom, which may be the same or different from each other, and at least two are hydrogen atoms. L is an integer of 0 to 1000, particularly an integer of 0 to 300, and M is an integer of 1 to 200.

[0079] (3) Catalyst component (Component C)

[0080] The catalyst component of component C can be a catalyst used in hydrosilation reaction. For example, platinum black, platinum chloride, chloroplatinic acid, a reaction product of chloroplatinic acid and a monohydric alcohol, a complex of chloroplatinic acid and olefins, vinyl siloxane, platinum catalysts such as bisacetoacetic platinum, palladium catalysts, rhodium catalysts and other platinum group metal catalysts can be listed. The two-liquid room temperature curing silicone polymer contains a platinum group metal catalyst, but the additional platinum group metal catalyst is used to control the curing speed.

[0081] (4) Thermally conductive particles (components B and C)

[0082] In the present invention, it is preferred that three or more inorganic particles having different average particle sizes are used in combination as thermally conductive particles. In the case of three types, they are component B-1, component C-1, and component C-2, and in the case of four types, component B-2 is added thereto. In this way, thermally conductive inorganic particles having a small particle size are buried between large particles, and filling can be performed in a state close to the closest packing, thereby increasing thermal conductivity.

[0083] (5) Other additives

[0084] The composition of the present invention may be formulated with ingredients other than the above as needed. For example, heat resistance improvers such as red iron oxide, titanium oxide, cerium oxide, flame retardant aids, curing delay agents, etc. may be added. For the purpose of coloring and toning, organic or inorganic pigments may be added. The above-mentioned silane coupling agent may also be added.

[0085] The following description will be given using the drawings. In the following drawings, the same reference numerals represent the same components. Figure 1 1 is a schematic cross-sectional view of assembling a heat conductive sheet in one embodiment of the present invention to a heat dissipation structure 10. The heat conductive sheet 11b dissipates heat generated by an electronic component 13 such as a semiconductor element, is fixed to a main surface 12a of a heat spreader 12 that is opposite to the electronic component 13, and is sandwiched between the electronic component 13 and the heat sink 2. In addition, the heat conductive sheet 11a is sandwiched between the heat spreader 12 and a heat sink 15. Moreover, the heat conductive sheets 11a and 11b together with the heat sink 2 constitute a heat dissipation component that dissipates heat from the electronic component 13. The heat sink 12 is formed in a square plate shape, for example, and has a main surface 12a that is opposite to the electronic component 13 and a side wall 12b that is erected along the outer periphery of the main surface 12a. The heat sink 2 is provided with a heat conductive sheet 11b on the main surface 12a surrounded by the side wall 12b, and a heat sink 15 is provided on the other surface 12c on the opposite side of the main surface 12a through the heat conductive sheet 11a. The electronic component 13 is a semiconductor element such as a BGA, and is mounted on a wiring board 14 .

[0086] Example

[0087] The following is an explanation using examples. The present invention is not limited to the examples. Various parameters were measured by the methods described below.

[0088] <Thermal conductivity>

[0089] The thermal conductivity of the thermally conductive silicone rubber sheet is measured by the transient plane heat source method (according to ISO22007-2:2008). Figure 2 As shown in Figure A, a polyimide film sensor 2 is sandwiched between two samples 3a and 3b, and constant power is applied to the sensor 2 to make it generate constant heat. The thermal characteristics are analyzed based on the temperature rise value of the sensor 2. The diameter of the front end 4 of the sensor 2 is 7 mm. Figure 2 As shown in B, the electrode has a double helical structure, and the current applying electrode 5 and the resistance value electrode (temperature measuring electrode) 6 are arranged at the bottom. The thermal conductivity is calculated by the following formula (Formula 1).

[0090] [Mathematical formula 1]

[0091]

[0092] λ: Thermal conductivity (W / m·K)

[0093] P0: Constant power (W)

[0094] r: Radius of the sensor (m)

[0095] τ:

[0096] α: Thermal diffusivity of the sample (m 2 / s)

[0097] t: measurement time (s)

[0098] D(τ): dimensionless function of τ

[0099] △T(τ): Temperature rise of sensor (K)

[0100] <Hardness>

[0101] The hardness of the thermally conductive silicone rubber sheet is measured according to SHORE 00.

[0102] <Plasticity>

[0103] Regarding plasticity, in accordance with JIS K 6300-3 and ISO2007:1991, using a Wallace plastometer, at a measurement temperature of 23°C, with a certain load (100 N) and a certain time (15 seconds), the thickness (t) of the specimen after compression between two metal plates is divided by the thickness (t0) before compression, and the resulting value is obtained as the plasticity (P0 = t / t0 × 100). The smaller the value of the plasticity (P0), the softer it indicates.

[0104] The plasticity before vacuum is the plasticity in the state where the composite is made. The plasticity after degassing is the plasticity after degassing for 5 minutes in a reduced-pressure state of -0.1 Pa after making the composite. Since the composite is formed into a sheet after degassing, the plasticity after degassing is important.

[0105] <BET specific surface area>

[0106] The BET specific surface area of the heat-conductive particles is measured in accordance with the provisions of JIS R1626-1996. The larger the value of the BET specific surface area, the smaller the D50 (median particle size) of the cumulative particle size distribution of the heat-conductive particles based on the volume basis.

[0107] (Examples 1 to 5, Comparative Examples 1 to 5)

[0108] 1. Material composition

[0109] (1) Polyorganosiloxane (Component A)

[0110] A two-component room-temperature-curing silicone polymer (silicone component) containing commercially available polyorganosiloxane is used. One liquid (Liquid A) contains a base polymer component (Component A1 in Component A) and a platinum-group metal catalyst, and the other liquid (Liquid B) contains a base polymer component (Component A1 in Component A) and an organohydrogenpolysiloxane as a crosslinking agent component (Component A2 in Component A). The ratio of Liquid A to Liquid B is A:B = 100:100 by mass.

[0111] (2) Heat-conductive particles (Component B)

[0112] The heat-conductive particles described in Table 1 are used. The average particle size is the D50 (median particle size) of the cumulative particle size distribution based on the volume basis in the particle size distribution measurement based on the laser diffraction light scattering method. As this measuring instrument, for example, there is a laser diffraction / scattering type particle distribution measuring device LA-950S2 manufactured by Horiba, Ltd. The numerical value before μm in the table is the average particle size of each particle.

[0113] (3) Heat-conductive particles (Component C)

[0114] The thermally conductive particles described in Table 1 were used. The average particle size is D50 (median particle size) of the cumulative particle size distribution based on the volume standard in the particle size distribution measurement based on the laser diffraction light scattering method. As the measuring instrument, for example, there is a laser diffraction / scattering particle distribution measuring device LA-950S2 manufactured by Horiba, Ltd. The values ​​before μm in the table are the average particle size of each particle. In addition, AlN in the table is an abbreviation for aluminum nitride.

[0115] (4) Platinum group metal catalyst (component C)

[0116] As an additional platinum group metal catalyst, a platinum-vinyl disiloxane complex was used. In addition, as described above, the two-liquid room temperature curing silicone polymer (silicone component) contains a platinum group metal catalyst. When preparing the silicone composition of each example, an additional platinum group metal catalyst was added to fully cure the polyorganosiloxane.

[0117] (5) Additive 1

[0118] As the unreacted silicone oil, dimethylpolysiloxane (using a Brookfield type rotational viscometer SP No. 2, viscosity at 25° C.: 100 mm 2 / s).

[0119] (6) Additive 2

[0120] Decyltrimethoxysilane was used as the silane coupling agent.

[0121] 2. Complex

[0122] The materials were weighed in the amounts shown in Table 1 and placed in a mixing device to prepare a composite. In Table 1, the amount of each material is recorded as the amount (parts by mass) when the silicone component (two-liquid room temperature curing silicone polymer) is 100 parts by mass (100 g). The composite was degassed at a reduced pressure of -0.1 Pa for 5 minutes.

[0123] 3. Sheet forming processing

[0124] The composite was sandwiched between a polyethylene terephthalate (PET) film subjected to a mold release treatment, and rolled into a sheet with a thickness of 2.0 mm using a constant speed roller at a temperature of 23°C and a roller speed of 0.5 m / min, and then heat-cured at 100°C for 15 minutes to obtain a thermally conductive silicone rubber sheet. The molding processability was judged as "possible" when molding was possible under the above conditions, and "NG" when molding was not possible.

[0125] The above conditions and results are shown in Tables 1 and 2. Tables 1 and 2 show the amount of each component added when the total of the base polymer component (A1), the crosslinking component (A2), the unreacted silicone oil and the silane coupling agent is 100 parts by mass.

[0126] Table 1

[0127]

[0128] Table 2

[0129]

[0130] As shown in Tables 1 and 2, it was confirmed that Examples 1 to 5 had high thermal conductivities and low plasticity of the compositions after degassing (plasticity before curing).

[0131] In contrast, since there is no B-1 component in Comparative Example 1, the plasticity is improved and the forming processability is NG. Comparative Example 2 does not have B-1 component, and even if the BET specific surface area is only increased, the plasticity is increased, and the forming processability is NG. In Comparative Example 3, the B component is lower than the lower limit, the plasticity is increased, and the forming processability is NG. In Comparative Example 4, the B component exceeds the upper limit, and the thermal conductivity is reduced. In Comparative Example 5, the C component is lower than the lower limit, and the thermal conductivity is reduced.

[0132] Industrial Applicability

[0133] The thermally conductive composition and the thermally conductive sheet of the present invention are suitable as a heat dissipation sheet: TIM (Thermal Interface Material) interposed between a heat generating portion of an electric or electronic component and a heat dissipator.

[0134] Reference numerals

[0135] 1Thermal conductivity measuring device

[0136] 2 Sensors

[0137] 3a, 3b samples

[0138] 4Sensor front end

[0139] 5 Electrodes for applying current

[0140] 6Resistance value electrode (temperature measurement electrode)

[0141] 10Heat dissipation structure

[0142] 11a, 11b Thermally conductive sheet

[0143] 12 Radiator

[0144] 13 Electronic components

[0145] 14 Wiring substrate

[0146] 15 Heat sink

Claims

1. A thermally conductive composition, characterized in that: The invention is a thermally conductive composition comprising a matrix resin (component A) formed of a thermosetting resin, a curing catalyst and thermally conductive particles. The thermally conductive particles include the following components B and C, (1) Component B: 220 to 500 parts by mass of aluminum oxide having a D50 (median diameter) of 0.01 μm or more and less than 1 μm in cumulative particle size distribution on a volume basis, based on 100 parts by mass of the matrix resin, comprising the following components B-1 and B-2, Component B-1: 30 to 100% by mass of component B with respect to 100% by mass of component B having a D50 (median diameter) of 0.01 μm or more and less than 0.3 μm, and a BET specific surface area of ​​9 m 2 / g or more of aluminum oxide, Component B-2: 0 to 70% by mass of aluminum oxide having a D50 (median diameter) of 0.3 μm or more and less than 1 μm, relative to 100% by mass of component B, (2) Component C: 1900 to 2500 parts by mass of aluminum nitride having a D50 (median particle size) of 0.01 μm or more and 150 μm or less, based on 100 parts by mass of the matrix resin, including the following components C-1 and C-2, C-1 component: D50 (median particle size) is 0.01 μm or more and less than 30 μm, Component C-2: D50 (median diameter) is 30 μm or more and 150 μm or less.

2. The thermally conductive composition according to claim 1, wherein The mass ratio of the C-1 component to the C-2 component is such that the C-2 component ≤ the C-1 component.

3. The thermally conductive composition according to claim 1 or 2, wherein The thermal conductivity of the cured product of the thermally conductive composition is 14 W / m·K or more.

4. The thermally conductive composition according to any one of claims 1 to 3, wherein The cured product of the thermally conductive composition has a SHORE 00 hardness of 75 or less.

5. The thermally conductive composition according to any one of claims 1 to 4, wherein The matrix resin is at least one selected from addition-cured silicone polymers, peroxide-cured silicone polymers and condensation-cured silicone polymers.

6. The thermally conductive composition according to any one of claims 1 to 5, wherein The present invention further comprises 0.1 to 10 parts by mass of a silane coupling agent based on 100 parts by mass of the base resin.

7. The thermally conductive composition according to any one of claims 1 to 6, wherein At least one component selected from the group consisting of aluminum oxide as the component B and aluminum nitride as the component C is in the form of amorphous crushed particles.

8. A thermally conductive sheet, characterized in that: The thermally conductive composition according to any one of claims 1 to 7 is formed into a sheet.

9. The thermally conductive sheet according to claim 8, wherein The thickness of the thermally conductive sheet is in the range of 0.2 to 10 mm.

10. A method for producing a thermally conductive sheet, characterized in that: The thermally conductive sheet is produced by vacuum degassing, rolling, and sheet forming the thermally conductive composition according to any one of claims 1 to 7, and then heating and curing the composition.

Citation Information

Patent Citations

  • Composition for thermal conducive grease, thermal conductive grease and heat dissipating member

    JP2016216523A

  • Light-emitting panel and building wall

    JP2018088416A

  • Absorbent article

    JP2020137970A

  • Silicone polymer and composition containing same

    JP2021518466A